HASIL DAN KANDUNGAN KOMPONEN SERAT KASAR HIJAUAN RUMPUT BENGGALA DENGAN PEMBERIAN MOLIBDENUM DAN JENIS LEGUM PADAPERTANAMAN CAMPURAN RUMPUT DAN LEGUM - Susilawati, Iin; Kemal Mustafa, Herryawan; Khairani, Lizah (Pastura, 2014)
The experiment was conducted to study the influence of molybdenum and legume genotype on yield of forage and components of crude fiber of benggala grass forage.The design of experiment was randomized block design (RBD), factorial pattern with 2 factors (3 x 4) and 3 replications. The first factor was consisted of four molybdenum fertilizer (m0 = without Mo; m1 = 3 g Mo per kg seed; m2 = 6 g Mo per kg seed; m3 = 9 g Mo per kg seed). The second factor was consisted of three legume genotype (l1 = kudzu/Pueraria phaseoloides; l2= kalopo/ Calopogonium mucunoides; l3 = 50% kudzu +50% kalopo). Molybdenum provided through seed treatment. Genotype of legume significantly affected on forage yield and not significantly affected on content of crude fiber components . Molybdenum fertilizer did not significantly affected the forage yield and content of crude fiber components of  benggala grass  forage.
Keywords: molybdenum, legume, forage yield, crude fiber components.